Divination in the ancient Near East : a workshop on divination conducted during the 54th Rencontre assyriologique internationale, Würzburg, 2008 - Fincke, Jeanette (Rencontre Assyriologique Internationale, 2014)
This volume contains a collection of revised papers given in the workshop Divination im Alten Orient that was convened on July 22, 2008, as part of the 54th Rencontre Assyriologique Internationale in Würzburg. The aim of this workshop was to bring together Assyriologists and Hittitologists in order to present and discuss the divination methods of their respective fields, most of which had not been studied until recently. The large audience that attended the workshop confirmed how wide is the interest in this subject.